Pengaruh Pengembangan dan Motivasi terhadap Prestasi Kerja Pegawai di PT. Bekasi Surya Pratama - Hendra Lesmana (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
This study aims to determine and analyze (1) the influence of development on employee job performance (2) the influence of motivation on employee job performance (3) the influence of development and motivation together towards achievement of employees in PT. Bekasi Surya Pratama. The experiment was conducted at PT. Bekasi Surya Pratama with 49 respondents and the research conducted from July to November 2010. The analysis is carried out linear regression analysis, analysis of determination, t test and F test. The hypotheses were (1) the influence of development (X1) will be increased employees job performance (Y) (2) the influence of motivation (X2) will be increased employees job performance (Y) (3) the influence of development (X1) and motivation (X2) are jointly working towards increased employees job performance (Y) in PT. Bekasi Surya Pratama. Based on the testing of the first hypothesis might be any positive and significant influence between development (X1 variable) with Job Performance (variable Y) of employees in the PT. Bekasi Surya Pratama based tcount of 2.142, was larger than ttable (ttable = 2.01). Thus the Ha accepted and H0 is rejected. Based on the testing of the second hypothesis might be any positive and significant influence between motivation (variable X2) with Job Performance (variable Y) of employees in PT. Bekasi Surya Pratama based tcount of 3.706, was larger than ttable (ttable = 2.01). Thus the Ha accepted and H0 is rejected. Based on the testing of the third hypothesis might be any positive and significant influence between development (variable X1) and Motivation (X2) with Job Performance (variable Y) of employees in the PT. Bekasi Surya Pratama based on the value of F test Based on calculations, the value of Fcount = 201.311. Fcount greater than Ftable (Ftable = 3.20). Thus the Ha accepted and H0 is rejected. The result of linear regression equations to show the effect of development (X1) and motivation (X2) on work performance (Y) employees in the PT. Bekasi Surya Pratama obtained Y = 2.491 +0.358 X1 +0.645 X2.